Analysis of the Relationship between Student Mental Health in Family Conflict and Bullying Among Students - Sumarmi, Sumarmi; Suyanti, Titi Sri; Janah, Esti Nur (Jurnal Pendidikan Progresif, 2024)
Abstract: This study aims to analyze the relationship between students' mental health in family conflict and bullying behavior among students, especially among male students in middle school. The research method used was quantitative with research subjects totaling 76 students who had bullying tendencies from a population of 450 people. Data collection was carried out through a questionnaire instrument to measure the stages of bullying behavior and investigation of family conflict violence with a Likert scale of 1-5. Descriptive and inferential statistical data analysis techniques (Pearson correlation test) were used to analyze the data. As a result, it was found that the level of bullying among male students tends to be low (2.52) and there is a significant relationship between family conflict and stages of bullying. Conflict between parents and students is the most frequent conflict, while conflict between siblings tends to be minimal. Family conflict factors need serious attention in designing intervention programs to prevent students' mental disorders through the phenomenon of bullying at school. Conclusion: This research emphasizes the importance of paying attention to family dynamics in understanding and overcoming bullying behavior in the educational environment. Identifying the relationship between family conflict and bullying tendencies can provide a basis for the development of appropriate interventions to create safe and supportive school environments for all students. Keywords: student treatment, exit conflict, student bullying tendencies, mental health.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202427